Analysis of the Effectiveness of Internal Control Roles Over Fixed Assets at the District Office of Medan Labuhan, North Sumatra - Pakpahan, Dewi; Gea, Stevan; Aisyah, Siti; Simatupang, Jumeida; Yanti, Aprili; Sembiring, Erika; Tamba, Iventura (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
This research aims to assess the effectiveness of the internal control system governing fixed assets at the Medan Labuhan District Office, identifying challenges, causes of ineffectiveness, and proposing strategies for improvement. The study employs a descriptive research approach and utilizes Nvivo+11 software for comprehensive analysis. Data are gathered through document analysis, interviews, and a review of Standard Operating Procedures (SOP) to evaluate the internal control system for fixed assets. The findings reveal that the internal control system at the Medan Labuhan District Office faces challenges, including inadequate communication on asset maintenance and negligence in financial record-keeping during asset transactions. These issues have led to operational inefficiencies and disputes, deviating from SOP. This study recommends solutions to prioritize communication regarding asset maintenance to enhance awareness and accountability. Additionally, it suggests implementing immediate and accurate recording practices to prevent disputes and discrepancies in financial documentation.